Selective inhibition of anti‐MAG IgM autoantibody binding to myelin by an antigen‐specific glycopolymer. Issue 5 (23rd June 2020) - Aliu, Butrint; Demeestere, Delphine; Seydoux, Emilie; Boucraut, José; Delmont, Emilien; Brodovitch, Alexandre; Oberholzer, Thomas; Attarian, Shahram; Théaudin, Marie; Tsouni, Pinelopi; Kuntzer, Thierry; Derfuss, Tobias; et al.
Abstract: Anti‐myelin‐associated glycoprotein (MAG) neuropathy is a disabling autoimmune peripheral neuropathy that is caused by circulating monoclonal IgM autoantibodies directed against the human natural killer‐1 (HNK‐1) epitope. This carbohydrate epitope is highly expressed on adhesion molecules such as MAG, a glycoprotein present in myelinated nerves. We previously showed the therapeutic potential of the glycopolymer poly(phenyl disodium 3‐ O ‐sulfo‐β‐d ‐glucopyranuronate)‐(1→3)‐β‐d ‐galactopyranoside (PPSGG) in selectively neutralizing anti‐MAG IgM antibodies in an immunological mouse model and ex vivo with sera from anti‐MAG neuropathy patients. PPSGG is composed of a biodegradable backbone that multivalently presents a mimetic of the HNK‐1 epitope. In this study, we further explored the pharmacodynamic properties of the glycopolymer and its ability to inhibit the binding of anti‐MAG IgM to peripheral nerves. The polymer selectively bound anti‐MAG IgM autoantibodies and prevented the binding of patients' anti‐MAG IgM antibodies to myelin of non‐human primate sciatic nerves. Upon PPSGG treatment, neither activation nor inhibition of human and murine peripheral blood mononuclear cells nor alteration of systemic inflammatory markers was observed in mice or ex vivo in human peripheral blood mononuclear cells. Intravenous injections of PPSGG to mice immunized against the HNK‐1 epitope removed anti‐MAG IgM antibodies within less than 1 hr, indicating a fast and efficient mechanism of action as compared to a B‐cell depletion with anti‐CD20. In conclusion, these observations corroborate the therapeutic potential of PPSGG for an antigen‐specific treatment of anti‐MAG neuropathy. Read the Editorial Highlight for this article on page 465 . Abstract : Anti‐MAG (myelin‐associated glycoprotein) neuropathy is a disabling autoimmune peripheral neuropathy that is caused by circulating monoclonal IgM autoantibodies directed against the HNK‐1 (human natural killer‐1) epitope. This glycoepitope is highly expressed on adhesion molecules such as MAG and is localized mainly in paranodal loops and Schmidt–Lantermann incisures of the peripheral nervous system. The glycopolymer PPSGG selectively bound anti‐MAG IgM autoantibodies and prevented the binding of patients' autoantibodies to myelin of primate sciatic nerves in the IFA (indirect fluorescents assay) anti‐MAG IgM assay (right panel). These findings corroborate the therapeutic potential of PPSGG for an antigen‐specific treatment of anti‐MAG neuropathy. Read the Editorial Highlight for this article on page 465 .